Nanoparticle-delivered antimicrobials for targeted suppression of bacterial wilt in peanut - Gelaye, Yohannes; Luo, Huaiyong (Frontiers in Microbiology, 2026)
Bacterial wilt caused by Ralstonia solanacearum is a major constraint to global peanut production, leading to serious yield and economic losses, particularly in tropical and subtropical regions. The disease reduces plant vigor, pod development, and overall productivity, posing a significant threat to food security and farmer income. Conventional control methods, including crop rotation, resistant varieties, soil amendments and chemicals, remain inconsistent and often provide limited long-term effectiveness. This inconsistency is due to the pathogen’s broad host range, prolonged soil survival, and high genetic adaptability, which enable rapid spread and persistence. These challenges indicate the need for sustainable alternatives that are effective and environmentally sound. Nanoparticle-based antimicrobial delivery systems have emerged as a promising strategy because of their precision targeting, improved stability, enhanced bioavailability, and controlled release of active agents. Key nanomaterial design parameters, including composition, size, surface functionalization, and carrier efficiency, critically influence antimicrobial activity against R. solanacearum. These characteristics affect interactions with bacterial cells and plant tissues. Major mechanisms of pathogen suppression involve membrane disruption, metabolic interference, oxidative stress generation, and induction of plant systemic resistance. Environmental aspects, such as nanoparticle fate, bioaccumulation, persistence in soil, and ecotoxicological risks, must also be considered to ensure ecological safety and sustainability. Integrating nanotechnology with plant breeding and biocontrol strategies can promote resilient and eco-friendly peanut production. Nanoparticle-enabled disease management offers a transformative approach for mitigating bacterial wilt while strengthening sustainable crop protection systems worldwide. Policy support and responsible innovation will accelerate the safe adoption of these technologies in the field.